Development of Education Personnel Competency Model at Airlangga University to Improve the Quality of Information Services in the Digital Society Era - Melinda, Rida Yutman (Jurnal Ilmiah Sumber Daya Manusia, 2023)
Airlangga University is one of the best universities in Indonesia, with various stakeholders and consumers from all over Indonesia and even from abroad. Of course, one of the keys to introducing the University to both local and global knowledge is the need for information services. Developments in information technology that are entering the digital society can be a way to facilitate information delivery; however, this technological development must be accompanied by the competence of information officers who have the task of conveying, informing, accommodating criticism and suggestions from stakeholders. The purpose of this study was to determine information officers' competence in improving service quality in the digital society era. This research uses descriptive qualitative by using descriptive by applying a review of several case studies and based on previous literature. The conclusion is that information officers must be able to improve their soft and hard skills in order to create services that are problem-responsive, effective, and efficient.